Play Therapy: Concepts and Techniques for Working with Divorce - Chafe, Don V. (Canadian Journal of Counselling and Psychotherapy, 2016)
Play therapy is an expressive arts therapy used primarily with children and families. It recognizes and adapts to the developmental needs of the child in therapy. As children grow and mature, their way of experiencing and understanding the world changes. This, of course, has a major influence on how they process environmental challenges such as divorce and remarriage. This article focuses on how to better understand children’s conceptualization of the effects of divorce on their world. It also explores some developmentally appropriate play therapy interventions that have the potential to help children make the best of the challenges set before them using the skills they have at their current developmental level.